Etika Bisnis pada Laksmi Muslimah - Lista Imanunah; Amin Sadiqin (JOURNAL OF ECONOMICS, BUSINESS, MANAGEMENT, ACCOUNTING AND SOCIAL SCIENCES, 2023)
Business ethics play a crucial role in regulating behavior in the business world. They influence the relationship between companies and their employees, as well as the relationships between companies and other economic actors. Business ethics rules are designed to facilitate the course of business, and compliance with these regulations can help companies achieve their goals. In Laksmi Muslimah, ethics are essential for carrying out operational activities, such as serving clients and dealing with them according to predetermined codes of ethics. This ensures that both customers and employees are comfortable in carrying out these activities. The research method used in this study is a qualitative method, using primary data obtained directly from Laksmi Muslimah as the main respondent through interviews, without going through intermediaries. In conclusion, business ethics are crucial for the success of any industry. Lakshmi Muslimah takes ethics seriously in all its operations, not just to make a profit. They guide clients on proper conduct through a predetermined Code of Conduct, ensuring safe activities for customers and employees. Lakshmi Muslimah communicates ethical standards actively through direct methods or WhatsApp groups. Violations result in sanctions for perpetrators.